A CHANGE OF THE PARADIGM OF THE FINANCIAL SYSTEM:THE FINANCIAL ARCHITECTONIC - Глущенко, О. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The evolution of scientific reflection of the financial system is investigational. It is marked divergence in interpretation of home and foreign authors. Certainly, necessary steps of transition from descriptive to the structural understanding of the financial system and the role of approach of the systems is considered. Turnover of concept «financial architectonic» is first entered and he is given authorial interpretation.